Natural deep eutectic solvents: solvents for the 21st century - Paiva, Alexandre (2014)
Green technology is actively seeking for new solvents able to replace common organic solvents which present inherent toxicity and have a high volatility, leading to the evaporation of volatile organic compounds to the atmosphere. Over the past two decades, ionic liquids (ILs) have gained enormous attention from the scientific community and the number of reported articles in the literature has grown exponentially. Nevertheless IL “greenness” is often challenged, mainly due to their poor biodegradability, biocompatibility and sustainability. An alternative to ILs are Deep Eutectic solvents (DES). Deep eutectic solvents are defined as a mixture of two solid components, which at a particular composition present a high melting point depression becoming liquids at room temperature. When the compounds that constitute the DES are primary metabolites, namely, aminoacids, organic acids, sugars or choline derivatives, DES are so- called natural deep eutectic solvents (NADES). NADES fully represent the green chemistry principles. Can natural deep eutectic solvents be foreseen as the next generation solvents and can a similar path to ionic liquids be outlined? The current state of the art concerning the advances made on these solvents in the past few years is reviewed in this Account. More than an overview on the different applications for which they have been suggested, particularly, biocatalysis, electrochemistry, extraction new data is presented in this work. Citotoxicity of different NADES was evaluated and compared to conventional imidazolim based ionic liquids and hints on the extraction of phenolic compounds from green coffee bean and on the foaming effect of NADES are revealed. Future perspectives on the major directions towards which the research on NADES is envisaged are here discussed and these comprised undoubtedly a wide range of chemical related subjects.